Manual de materiales didácticos para la estimulación multisensorial en infantes de 0 a 2 años, 2019 - Reyes Espejo, Yackelyn Yessenia (2020)
The hereby descriptive research considers the importance of multisensory stimulation in young children between 0 to 2 years old for the improvement of learning and the maximum development of their competences. In the theoretical framework of this piece of work, a series of activities and suitable materials to conduct the multisensory stimulation will be presented. The objective of this investigation is to strengthen the multisensory stimulation in infants throughout the elaboration of a manual with a variety of materials that will allow to develop students’ different intelligences, autonomy, self-esteem, and potentials, what lead us to redefine our pedagogical action in terms of students’ learning necessities. It proposes a manual of educational materials considered for the multisensory stimulation, highlighting the importance of working with infants under two years old. This is a basic investigation whose type of study in bibliographic. In this investigation, books, thesis, guides, internet and magazines were used.